2021
DOI: 10.24251/hicss.2021.816
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Stakeholders in Agile Information Systems Development Projects: A Mixed Methods Approach

Abstract: Agile information systems development (ISD) strives for a high amount of interaction between the agile team and stakeholders to ensure that high quality software within commonly defined project goals is produced. The literature has acknowledged that agile ISD significantly changes the work of team members. How do agile practices affect the work of stakeholders? Unfortunately, little theory exists to answer this question. This paper addresses this gap by investigating the effect of agile practices on stakeholde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Since studies have shown that failing in ISD projects can lead to a positive learning success, this approach promises beneficial long-term effects [7]. One of the striking aspects of agile ISD is to increase outcomes at work, such as motivation and job satisfaction [8][9][10]. The Agile Manifesto claims to value individuals and interaction over processes and tools.…”
Section: Introductionmentioning
confidence: 99%
“…Since studies have shown that failing in ISD projects can lead to a positive learning success, this approach promises beneficial long-term effects [7]. One of the striking aspects of agile ISD is to increase outcomes at work, such as motivation and job satisfaction [8][9][10]. The Agile Manifesto claims to value individuals and interaction over processes and tools.…”
Section: Introductionmentioning
confidence: 99%